Heterogeneity in Vision, Hand Function, Cognition, and Health Literacy Among Older Veterans: Impacts, Outcomes, and Clinical Recommendations for First-Time Hearing Aid Users - Saunders, Gabrielle H.; Grush, Leslie; Vachhani, Jay; Echt, Katharina V.; Griest, Susan; Lewis, M. Samantha (Journal of the American Academy of Audiology, 2021)
Background Age-related changes (both normal and pathological), and health literacy are relevant to audiological practice. Changes associated with the musculoskeletal, vascular, and nervous systems drive manual, visual, and cognitive function. These in turn affect the capabilities required for effective hearing aid (HA) skill acquisition, use, and management. Meanwhile, health literacy influences the ability to gain access to, understand, and use information, which is important for promoting and maintaining HA use and management. Understanding the interindividual variability of these variables can help audiologists characterize those individuals who might have suboptimal HA outcomes. This knowledge can then inform better clinical practices and guide implementation of processes to improve care quality and outcomes.Purpose The aim of the study is to assess the variation in manual, visual, and cognitive function, and health literacy, among community-dwelling older individuals, and to determine whether and which of these variables are associated with reported HA outcome and/or the knowledge and skill to manage HAs.Research Design Data presented here were collected as part of an efficacy trial of four variants of HA orientation. The data were collected at baseline (prior to HA fitting) and after 4 to 8 weeks of HA use.Study Sample The study sample consists of 265 U.S. Veterans aged 51 to 87 years with no previous HA experience who were scheduled to receive their first pair of HAs from the Veterans Administration.Data Collection and Analysis We assessed baseline measures of hand function, vision, cognition, and health literacy just prior to participants receiving their first pair of HAs. HA management skills and knowledge, and HA outcome were measured after 4 to 8 weeks of HA use using the Hearing Aid Skills and Knowledge (HASK) and International Outcomes Inventory for Hearing Aids (IOI-HA), respectively. Data collected here was compared with published norms to assess variation in baseline measures. Associations between baseline performance and outcomes data were examined using t-tests comparing participants who performed at or above age-based norms with those who performed below age-based norms.Results Participants' performance on the baseline measures was highly variable, with the proportions of individuals performing below norms varying by test measure. When combining data across the nine baseline measures, approximately 10% of participants performed below published norms on five or more measures, and 85% performed below norms on at least one measure. Poor manual dexterity, ability to learn a new task, and ability to draw inferences from spoken information negatively impacted HA management and outcome.Conclusion There was a considerable heterogeneity among a community-dwelling sample of first time HA users in terms of sensory, cognitive, and motor function. Clinicians should consider modifying their clinical practice to account for such heterogeneity and best support their patients in adapting to new HAs.
Keywords: hearing aids; auditory rehabilitation; individual differences